The top tier of the Big Five does not predict police decisions in ambiguous and high-pressure situations - Ricardo Tejeiro; David McIlroy; Marek Palace; Rui Paulo; José Luis González Álvarez (Cogent Social Sciences, 2024)
Whilst the link between personality and decision-making has been studied across various domains, the predictive capability of the Big Five model (openness to experience, extraversion, agreeableness, conscientiousness and neuroticism) for police decisions in high-risk ambiguous situations under time pressure remains unexplored. One-hundred and fifty-six cadets in a Spanish police force’s commanders’ school (78.8% male, aged 21–54) responded to two expert-designed policing scenarios necessitating quick decisions in ambiguous and high-risk conditions, where they had to act or wait for more information through different stages. They then completed the Mini-IPIP. Statistical tests revealed no significant relationships between the Big Five and (a) participants’ decision timing or (b) the appropriateness of their decisions (all p > 0.05). Linear regressions found no mediation by participants’ gender or prior experience. The predictive power of the top tier of the Big Five in these scenarios is not supported; consideration is given to analysing at the facet or subdimension level.